Risk indicators associated with tooth loss in Jordanian adults - Hamasha AH, Sasa I, Al Qudah M (Blackwell Synergy, 2000)
The purpose of this study was to evaluate the risk indicators of tooth loss in Jordanian adults. Methods: A sample of 509 Jordanian adults was randomly selected. The subjects were interviewed regarding demographics, social economic status, smoking habits, and oral hygiene practices and then clinically examined by a single examiner. Multiple regression analysis was performed to estimate the simultaneous impact of risk indicators on tooth loss. Results: The subjects’ mean age was 42.6 years with an average of 20.9 teeth remaining per person.